Yuri Alexandrovich Novikov (30.10.1938 – 12.01.2023) - Morozova, Nadežda (Slavistica Vilnensis, 2023)
Yu. A. Novikov is an outstanding researcher of the Old Belief in Lithuania and, more broadly, in the Baltic countries. Actively engaged in the study of folklore in different regions of Lithuania, he left behind an invaluable scientific heritage, which for many years will be in demand by everyone who investigates the problems of history, folklore, the language of old belief in the Baltic countries.